IMPLEMENTASI MARKETING MIX SYARIAH DI ERA INDUSTRI 4.0 PERSPEKTIF HUKUM EKONOMI SYARIAH - asofik, rifan; syaiin; afif, abdullah (Irtifaq, 2020)
The industrial age 4.0 consumer was more suited to social opinion. In fact, the most personal purchasing decisions are essentially social decisions. Consumers communicate with each other about products from each company. Based on the marketing communication point of view, consumers are no longer a passive target but an active medium of communication. Marketers should accept shifts to the more horizontal, inclusive, and social landscape of business. Markets are increasingly inclusive, social media removing geographical and demographic barriers, enabling people to communicate and innovate through collaboration. The study aims to know the implementation of islamic marketing mix in the industrial 4.0 and the marketer strategy in the digital market perspectives on islamic economic law. To address both issues, researchers use library research approach, the research which approach that uses books as their source. By emphasizing the tracking and study of literature and literary materials consistent with the marketing mix of sharia in the industrial 4.0 and the marketer strategy in the digital market perspective on islamic economic law. Both the books on sharia marketing and islamic economic law and the accompanying literature as a complement and comparison. Key words: implementation, marketing mix sharia, islamic economic law